Making and Managing Knowledge in the “New” Humanities: An Australian Experience - Bennett, Dawn (Common Ground Publishing Pty Ltd, 2011)
The innovative ways in which humanities academics give shape and meaning to traditional and artistic research has attracted increasing attention as researchers address ever-more complex issues. This attention stems in part from the problematic frameworks in which academic research is situated, but it relates also to growing concerns that traditional “scientific” research approaches do not always provide an adequate model for research, including some of what is happening in the sciences. In this paper the focus is on knowledge relating to artistic research. Implications include managing the translation of artistic research into a form that can be understood (and learned from) by the wider academy, and accommodating artistic research output within research frameworks less flexible than the works they assess.